Developing the Prototype of Text-Based Learning Materials for the Teaching of Reading Skills at the Middle Schools - Ahmad Habibi; Jupri; Sadaf Dehghani (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
The objectives of this research are to find out the learning needs of students of VIII grade in improving their reading skills and to develop suitable reading learning materials using a genre-based approach for students in the second semester of the middle schools. This research is categorized into research and development (R & D). The steps of this research are needs analysis, product development, evaluation by the expert, revision, and final product design. The data were in the form of quantitative data obtained using a questionnaire and qualitative in the form of open-ended questions, then the reading materials were revised based on the experts’ suggestions. This study indicated each chapter contained: chapter number and chapter title, let's start, let's learn the model, let's work together, let's create and improve, follow-up, let's reflect, let's summarize, and mini dictionary as that the appropriate supplementary reading materials concerning the text-based reading materials were successfully developed through development models, namely Define, Design, Develop, and Disseminate (Four-D Model). Finally, the developed materials are considered appropriate for the subjects of the study based on the results from the expert judgment questionnaire. The aspects of this questionnaire were content, instructional design, language, learning resources, and graphics. It can be concluded from this data that each aspect of the developed materials was considered